Repairing dan Relokasi Alat Pendeteksi Banjir Desa Bogoharjo Kecamatan Ngadirojo Kabupaten Pacitan - Nuril Esti Khomariah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
This program is used to assess the time of high tide with excessive volume discharge that can cause flooding in Punjul hamlet that can impact to all areas around the village. The method used is to observe directly in the area around the hamlet and directly - carried out the practice of repair, removal and re-installation of flood detection equipment. This flood detector is repaired and assembled using a water sensor functionally illuminated and emits an alarm when the water level rises with the gain reaching approximately. 15 m above the height of river water in the hamlet punjul.Keywords : river, repair, pacitan.